DYNAMICS OF EXPLOSIVE POWER DEVELOPMENT IN YOUNG ATHLETES - Tereza Marinova (Scientific Publishing House. NSA Press, 2023)
To better understand the selection processes and a controversial orientation in track and field, we set ourselves the goal of Establishing the periods of the highest age-related increase in speed and power abilities in adolescent athletes. The following tasks of the study were derived from that goal: (1) To determine the dynamics of increase in the explosive power, and (2) To determine the main periods of its development. The study population consisted of 245 children between 7 and 12 years of age. The measured indicators were reported by Optojump Next and the obtained results were subject to statistical analysis. Jump height ranged between 20.5 cm and 29.1 cm for boys and between 22.6 cm and 31.0 cm for girls. The RSI was in the range of 0.50-1.26 for boys and 0.71-1.24 for girls. Conclusions: (1) The period around the age of 10 appears to be sensitive for developing the explosive power abilities of adolescents; (2) Drop jump from a height of 30 cm is a more suitable speed and power exercise for girls